Pemberdayaan Masyarakat Dalam Pemberantasan Penyalagunaan Narkoba/Narkotika Demi Mewujudkan Desa Bersinar Melalui Kegiatan Sosialisasi Pada Remaja Dan Pemuda - lydia Surijani Tatura; Ernawati Ernawati (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
The 2021 Thematic Community Service Program is oriented to assists the community in combating drug abuse which is currently rife in society. The form of community service programs carried out is in the form of community empowerment in eradicating drug/narcotics abuse in order to realize a Desa Bersinar (Drug Clean Village) through outreach activities to Teenager and Youth (Remamuda) in Moluo Village, Kwandang District, North Gorontalo Regency. This activity was attended by 15 students as participants of the Thematic Community Service Program with 45 days of implementation at the service location. The method used in this program is socialization for the community, with the flow of activities namely preparation and debriefing of KKNT Bersinar Village students, then continued with the implementation of socialization to the community, especially Teenager and Youth (Remamuda). With community participation in this activity, it is especially beneficial for teenager and youth in Moluo village.